2021
DOI: 10.1021/acs.jpca.1c01412
|View full text |Cite
|
Sign up to set email alerts
|

Role of Charge Transfer in Halogen Bonding

Abstract: Halogen bonding has received intensive attention recently for its applications in the construction of supramolecular assemblies and crystal engineering and its implications and potentials in chemical and biological processes and rational drug design. Peculiarly, in intermolecular interactions, halogen atoms are known as electron-donating groups carrying partial negative charges in molecules due to its high electronegativity, but they can counterintuitively act as Lewis acids and bind with Lewis bases in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 98 publications
3
33
0
Order By: Relevance
“…The more the charge transfer, the larger the second order perturbation energy (Δ 2 E ), the lower the reaction energy barrier, and the better the catalytic activity of the halogen bond donor. This illustrates that charge transfer 82 is significant for the activation of the reactant with catalysts, which is consistent with the study by Kozuch and Huber. 75 The catalysis of halogen bonds activates the carbonyl oxygen atom in the Michael addition reaction, which is used to accelerate the reaction by promoting the charge transfer from indole to the Michael acceptor, thereby accelerating the formation of the carbon–carbon bond.…”
Section: Resultssupporting
confidence: 92%
“…The more the charge transfer, the larger the second order perturbation energy (Δ 2 E ), the lower the reaction energy barrier, and the better the catalytic activity of the halogen bond donor. This illustrates that charge transfer 82 is significant for the activation of the reactant with catalysts, which is consistent with the study by Kozuch and Huber. 75 The catalysis of halogen bonds activates the carbonyl oxygen atom in the Michael addition reaction, which is used to accelerate the reaction by promoting the charge transfer from indole to the Michael acceptor, thereby accelerating the formation of the carbon–carbon bond.…”
Section: Resultssupporting
confidence: 92%
“…However, it must be underscored that the shift patterns in Figure include not only the intermolecular transfer but also the internal reallocations within each monomer. And as recently demonstrated by Inscoe et al, who separated these two types of shifts from one another for halogen bonds, these two phenomena oppose one another in the intermolecular region, where it is the polarization that is the stronger of the two. The pattern of charge shifts documented in Figure , especially the internal polarizations, is not entirely unlike that observed in σ-hole interactions.…”
Section: Resultsmentioning
confidence: 74%
“…The intensive scrutiny of σ-hole bonds has led to a solid understanding of the fundamental phenomena from which they draw their strength. The chain of processes, beginning with the distortion of the σ­(R–X) covalent bond arising from the R–X electronegativity difference, and the resulting σ-hole in the density, which in turn leads to the positive potential, have been characterized. ,,, Also studied extensively has been the relationship between the magnitude of the σ-hole potential and the strength of the ensuing interaction with a nucleophile and how other factors enter into the equation such as charge transfer and dispersion. , Research has also built a body of understanding of the effects of the σ-hole bond on the intermolecular distance and perturbations within the individual monomers, both geometric and spectroscopic. …”
Section: Introductionmentioning
confidence: 99%
“…In each of the chalcogen, pnicogen, tetrel, and triel bonds, an atom of that same particular family of the periodic table replaces the bridging proton of the H-bond. Among these interactions, the halogen bond (XB) is arguably the one that has been acknowledged for the longest time and has engendered the greatest amount of scrutiny. Extensive study has demonstrated that the XB owes its stability to several factors. In the first place, the electron-density cloud surrounding the X atom is quite anisotropic; while the overall charge on the X atom is partially negative, there is a pocket of positive potential that lies along the extension of the covalent C–X bond, which is commonly referred to as a σ-hole. This positive region attracts the negative potential of an approaching nucleophile, for example, its lone pair, leading to a Coulombic attraction.…”
Section: Introductionmentioning
confidence: 99%